Accounting information systems - Richardson, Vernon J.; Chang, C. Janie; Smith, Rodney (Business writer) (New York, NY : McGraw-Hill Education, 2021)
"Whether accountants work in public accounting or in industry, they use a variety of technology tools. The International Federation of Accountants (IFAC) describes four roles for accountants with respect to information technology: (1) users of technology and information systems, (2) managers of users of technology and related information systems, (3) designers of information systems, and (4) evaluators of information systems. As users, managers, designers, and evaluators of technology and technology-driven business processes, accountants must understand the organization and how organizational processes generate information important to management. To ensure that processes and systems are documented-and to participate in improvements to processes and systems-accountants must be business analysts. This text aims to provide students with a variety of technology and business analysis concepts and skills. It is intended for use in the first Accounting Information Systems course at both the undergraduate and graduate levels. Ongoing changes in business technology-such as the move to Internet-based systems, Big Data and Data Analytics, software as a service, and mobile access to enterprise information, as well as increased security and control requirements-make technological skills more important than ever for accounting graduates. This text also aims to show how current changes in accounting and technology affect each of these roles. For example, the Sarbanes-Oxley Act affects financial reporting system controls, and XBRL changes system requirements and affects how companies develop and report financial information. We also consider the role of Big Data and Data Analytics and how they are used in financial accounting, managerial accounting, and auditing. Additionally, we consider both the COBIT and COSO frameworks to describe how organizations deal with risk management. In their roles as managers, designers, and evaluators, accountants must know how those frameworks affect their accounting and related information systems"--
Includes index.
Keywords: Accounting -- Data processing; Information storage and retrieval systems -- Accounting